Imaginário social e formação continuada: o olhar para as discussões de gênero, etnia e diversidade sexual - Machado, Gabriella Eldereti (2018)
This research is part of the Graduate Program in Education of the Federal University of Santa Maria, held in the Master in Education, in the Line of Training, Knowledge and Professional Development. It aimed to know through cinema in the training of teachers their imaginary meanings in relation to the issues of gender, ethnicity and sexual diversity that permeate schools and the daily life of students. Using as a methodological contribution the Autobiographical Research, through authors like: Delory-Momberger (2012; 2014); Josso (1999, 2002, 2004, 2006, 2007); and cinema as a training device in the studies of Souto (2007). In relation to the Social Imaginary, it is based on the studies of Castoriadis (1982); Silva (2017); Oliveira (2014); Teixeira (2005, 2006). In order to think about teacher education, we have as theoretical contribution Ferry (2004) and Nóvoa (1995) and in the aesthetic ethical context Hermann (2005). On the issues of gender, ethnicity and sexual diversity, the theoretical framework is based on: Davis (1982); Scott (1995); Louro (1997); Butler (2003); Precious (2011, 2017). On film, I bring Law nº 13.006 and the basis in the studies of Fresquet (2015) and Morin (1989; 1997), as well as studies carried out by GEPEIS members. Thus contextualizing the themes of gender, ethnicity and sexual diversity in the space of continuing education of teachers from two schools in the city of Santa Maria/RS. This research had twenty - one (21) collaborating teachers from both schools, carrying out the research - training process in four (04) continuing education meetings. The research findings permeate three moments of the research: the first one, in the meetings with the cinema and the groups of teachers being able to carry out the discussion of the themes from the short ones that were attended; the Deck of Imaginary Social Meanings creating another form of interview and narrating; and the letters as provocative the narrative of life and formation.